Get Answers to all your Questions

header-bg qa

Q2 Factorise  

(V)

(l+m) ^ 2 - ( l- m ) ^2

Answers (1)

best_answer

We have, 
             (l+m) ^ 2 - ( l- m ) ^2  = [(l + m) - (l - m)][(l + m) + (l - m)]                                                                                                                 (using  a^{2} - b^{2} = (a-b)(a+b) )
                                                       = (l + m - l + m)(l + m + l - m)
                                                       = (2m)(2l) = 4ml

Posted by

Gautam harsolia

View full answer